Antibiotic Resistance in the Elderly - Yvonne Dabota Buowari (Journal Of Aging Research And Healthcare, 2017)
This is a short communication article on antibiotic resistance in the elderly. The elderly is prone to infections and therefore the use of antibiotics in the elderly is common. Literature review was done using Medline, Google and PubMed.
Keywords: Elderly